The Effect of Wom And Advertising on Purchase Intention With Brand Awareness As Mediating Variable At Five Star Restaurants In Nusa Dua - Arini Ameswari; Chablullah Wibisono; Elli Widia (Publikasi Indonesia, 2021)
The research was conducted to see the effect of work environment, motivation, and workculture on employee performance through job satisfaction as an intervening in at PT. BankTabungan Negara (PERSERO) TBK. The research method used is descriptive quantitative bycollecting data and testing hypotheses and providing conclusions from the results of the study using a questionnaire. Respondents in this study were employees who worked at PT. Bank Tabungan Negara (PERSERO) TBK Batam Branch, totaling 124 respondents. Path coefficient calculation using SEM test assisted by AMOS version 24.0. To determine the direct and indirect effect between variables, it is seen from the results of the calculation of the path coefficient and to determine the significance. Changes in job satisfaction are influenced by the work environment, motivation, and work culture by 16.5%, and the rest is influenced by other factors not examined in this study by 27.3%. Meanwhile, changes in employee performance are influenced by the work environment, motivation, and work culture by 3%, and the rest is influenced by other factors not examined in this study.